Factors Affecting Delayed Graduation of Professional-Stage Dental Students: A Qualitative Study - Agus Ardinansyah; Nurhidayati Nosi; Ichasia Dwiheza Chairunnisa (YARSI Dental Scientific Meeting - e Journal, 2025)
Timely graduation in professional dental education is an indicator of clinical learning success and the development of student competencies; however, delayed graduation remains common across dental faculties in Indonesia, influenced by both internal and external factors. This study aimed to identify factors contributing to delayed graduation among professional-stage dental students at YARSI University Faculty of Dentistry using a descriptive qualitative approach with a phenomenological design. Data were collected through Focus Group Discussions (FGDs) with students and in-depth interviews with academic staff and program administrators, followed by thematic analysis. Results indicated that internal factors included learning motivation, psychological condition, clinical skills, communication abilities, and time management, while external factors encompassed patient availability and compliance, faculty policies and discipline, clinic service management, infrastructure, and curriculum regulations, with complex interactions between internal and external factors affecting clinical education progress. In conclusion, delayed graduation among professional-stage dental students is influenced by a combination of internal factors such as motivation, psychological condition, clinical self-confidence, communication skills, and time management, as well as external factors including inconsistent faculty supervision, clinic service systems, requirement policies, patient availability, and financial burdens.